DINAMIKA KECEMASAN AKADEMIK PADA MAHASISWA BERPRESTASI YANG MENGALAMI IMPOSTOR SYNDROME - Nurfadhilah, Arum; Archianti, Puti (Jurnal Psikologi, 2024)
Impostor syndrome is a psychological phenomenon where a person cannot accept their achievements. This phenomenon is closely related to anxiety. In students, the form of anxiety associated with Impostor syndrome is academic anxiety. The research conducted aims to determine the dynamics of academic anxiety in high-achieving students who experience Impostor syndrome. The method used in the research is qualitative with a phenomenological approach to reveal the meaning of a phenomenon. The data collection method used was non-probability sampling with a purposive sampling technique.  The subjects in the study consisted of three students who experienced academic anxiety with impostor syndrome tendencies. The results showed that the dynamics of academic anxiety of subjects who experience Impostor syndrome have the same pattern which begins with a change in academic role that triggers feelings of impostor syndrome which ultimately forms academic anxiety that inhibits individuals from completing tasks and utilizing their potential, thus harming the subject's psychological, physical, and cognitive.